How effective are EU minimum energy performance standards and energy labels for cold appliances? - Joachim Schleich; Antoine Durand; Heike Brugger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
In most countries, minimum energy performance standards (MEPS) and energy labels are the key policies to accelerate the diffusion of energy-efficient appliances and to help meet energy efficiency and climate policy targets. This paper estimates country-specific multivariate econometric models for eight EU countries over the period of 2007 to 2017 to evaluate the combined effects of changes in the MEPS and the energy labels entering into force in the EU in 2010 and 2011. The findings suggest that these policies increased the market share of cold appliances (refrigerators and fridge-freezer combinations) with an energy label of A+ and better between about 15 and 38 percentage points. For these appliances, autonomous developments (captured through a time trend) are estimated to range between 5 and 10 percentage points per year. Thus, failure to account for autonomous developments would have resulted in substantially overestimating the combined effects of MEPS and energy label policies in the EU. The findings further imply that policy evaluations should allow for policy effectiveness and autonomous developments to differ across countries.
urn:nbn:de:0011-n-6154104
Keywords: 330; energy efficiency; energy labelling; minimum energy performance standards; policy evaluation